Gambaran Hasil Pemeriksaan HBSAG pada Pendonor di Unit Donor Darah Palang Merah Indonesia Kabupaten Kudus - Catur Retno Lestari; Arief Adi Saputro (Jurnal Health Sains, 2021)
Hepatitis B is an infectious disease that attacks the liver which can be acute and chronic. Blood transfusion is one of the most common horizontal HBV transmission routes. In donors who suffer from hepatitis B disease or become carriers of hepatitis B, the blood containing the hepatitis B virus can be transmitted to recipients through blood transfusions. Several measures are taken to prevent the transmission of hepatitis, namely by checking for HBsAg. If HBsAg is positive, the donor is not allowed to donate. The purpose of this study was to find out an overview of the results of HBsAg examination on donors at the Indonesian Red Cross Blood Donor Unit, Kudus Regency during 2020. Donors at the Kudus Regency Blood Transfusion Unit during 2020. The study was carried out in January 2021 at the Kudus Regency Blood Transfusion Unit. . Diagnostic tests are performed using the Frequency Distribution. The results showed that the number of reactive donors was 96 (0.60%) of the total 16,081 donors. The number of reactive donors was more in males, namely 78 (81.25%) of the total reactive donors, while 18 (18.75%). Reactive HBsAg cases with the most donors were in February 2020 and the lowest cases were in November 2020. Hepatitis B affects men more than women. This is because men are generally more active than women, while hepatitis is transmitted through bodily fluids, which may occur due to activity, for example, through wounds received at work or while shaving.